132 Concentrations of circulating pregnancy-associated glycoprotein differs between cows receiving Bos indicus vs. Bos taurus embryos. (7th December 2018) - Fontes, P; Oosthuizen, N; Ciriaco, F; Henry, D; Sanford, C; Canal, L; Pohler, K; Mercadante, V; Ealy, A; Johnson, S; DiLorenzo, N; Lamb, G
Abstract: Our objective was to evaluate the effects of Bos indicus and Bos taurus genetics, as well as dietary energy, on plasma concentrations of pregnancy-associated glycoproteins (PAG). Reciprocal embryo transfers were conducted in a completely randomized design with a 2 × 2×2 factorial arrangement of treatments to generate pregnancies (n=55). Recipient cows were placed into a facility equipped with a feed intake monitoring system, and assigned to: 1) a diet to meet maintenance requirements (MAINT), or 2) a diet that restricted intake energy to 70% of maintenance requirements (RESTR). Angus (AN) and Brangus (BN) female in vivo produced embryos were transferred on d 7 to either AN or BN recipients fed the respective diets for 27 d. Blood samples were collected weekly from d 28 to 91, and two commercial (A1 and A2) and one in-house ELISA were used to determine concentrations of PAG. The assays differed in the antibody combination used, resulting in the detection of different PAG. An embryo breed×day interaction was observed in A1, where cows receiving BN embryos had greater concentrations of PAG at d 91 ( P PPP> 0.10). Therefore, embryo breed is likely responsible for the previously observed differences in concentration of PAG between Bos indicus and Bos taurus cattle. In addition, differences in circulating PAG depend on the antibody used in the assay, indicating that the profile of PAG production differs between subspecies.